2016
DOI: 10.1016/j.stemcr.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Hematopoietic Stem Cell Transplantation Fails to Fully Regenerate the B-Lymphocyte Compartment

Abstract: SummaryB cells are key components of cellular and humoral immunity and, like all lymphocytes, are thought to originate and renew from hematopoietic stem cells (HSCs). However, our recent single-HSC transfer studies demonstrate that adult bone marrow HSCs do not regenerate B-1a, a subset of tissue B cells required for protection against pneumonia, influenza, and other infections. Since B-1a are regenerated by transfers of fetal liver, the question arises as to whether B-1a derive from fetal, but not adult, HSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 56 publications
6
67
4
Order By: Relevance
“…Evidence for this mechanism in humans was recently supported by studies of human T-cell development (Mold et al, 2010). Our discovery of a fetal HSC characterized by lower CD150 expression with distinct innate-like lymphocyte potential is also consistent with a recent report demonstrating that B1 B-cell regenerative capacity mainly reside outside the conventional fetal HSC compartment (Ghosn et al, 2016). The coincidence in existence of the GFP+ HSCs with the perinatal burst in lymphoid development suggests that these HSCs play important roles in specifying innate-like B- and T-cells, while also contributing to robust establishment of adaptive immunity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Evidence for this mechanism in humans was recently supported by studies of human T-cell development (Mold et al, 2010). Our discovery of a fetal HSC characterized by lower CD150 expression with distinct innate-like lymphocyte potential is also consistent with a recent report demonstrating that B1 B-cell regenerative capacity mainly reside outside the conventional fetal HSC compartment (Ghosn et al, 2016). The coincidence in existence of the GFP+ HSCs with the perinatal burst in lymphoid development suggests that these HSCs play important roles in specifying innate-like B- and T-cells, while also contributing to robust establishment of adaptive immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, despite lower overall reconstitution levels and limited long-term reconstitution upon in utero transplantation (IUT) (Figure 7H and Table S4), GFP+ KLS cells still retained a greater capability to seed the peritoneal IgM+ B-cell compartment and particularly B1a cells as compared to Tom+ KLS cells upon IUT (Figure 7I). Although a recent report suggested that fetal HSCs are not a major source of B1a cells (Ghosn et al, 2016), we did not observe appreciable regeneration of innate-like B-cells in the absence of LTMR and BM reconstitution (Figure S5). Secondary recipients that did not demonstrate LTMR showed limited ability to reconstitute innate-like lymphocytes in vivo (Figure S5D).…”
Section: Resultscontrasting
confidence: 77%
“…Recent reports have strengthened the concept that adult HSCs do not contribute significantly to the innate B-1a cell compartment, but suggest heterogeneity in the fetal HSC compartment with regard to B-1a cell potential (Beaudin et al., 2016, Ghosn et al., 2012, Ghosn et al., 2016, Kristiansen et al., 2016, Sawai et al., 2016). Previous studies by members of our group identified an embryonic HSC-independent B cell progenitor with B-1 but not B-2 cell potential (Kobayashi et al., 2014, Yoshimoto, 2015, Yoshimoto et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated B-1a cells develop prior to emergence of hematopoietic stem cells in the yolk sac (YS) and para-aortic splanchnopleura (PSp) endothelium (47, 48). These embryonic and fetal derived B-1 cells are maintained in the adult by self-renewal.…”
Section: Discussionmentioning
confidence: 99%